2016
DOI: 10.1111/1365-2745.12660
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of plant defences along an invasion chronosequence: defence is lost due to enemy release – but not forever

Abstract: Summary1. The success of invasive plants has often been attributed to their rapid evolution at the introduced range. In particular, release from native enemies has been suggested to select for an evolutionary shift in resource allocation patterns from herbivore defence to increased size. Such evolutionary processes can take place not only between the native and invasive ranges but also within the invasive range over time, but this premise has been very seldom studied. 2. In this study, we examined the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 78 publications
(191 reference statements)
2
46
0
1
Order By: Relevance
“…Taking into account our results and those from Switzerland, we can speculate that, since I. glandulifera had become acclimated to higher pressure in its primary area of occurrence, its success was driven not only by release from enemies but also by higher tolerance of the negative effects of their presence, which would be consistent with the assumptions by Schierenbeck et al [79] and the enemy tolerance hypothesis [80]. In line with this, Gruntman et al [44] found that herbivore pressure on I. glandulifera in the introduced range increased with age of populations, with the highest levels noted for those 45-65 years old. However, herbivore pressure for the oldest populations (65-85 years) sharply fell to the lowest level, equal to the level noted for native populations.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Taking into account our results and those from Switzerland, we can speculate that, since I. glandulifera had become acclimated to higher pressure in its primary area of occurrence, its success was driven not only by release from enemies but also by higher tolerance of the negative effects of their presence, which would be consistent with the assumptions by Schierenbeck et al [79] and the enemy tolerance hypothesis [80]. In line with this, Gruntman et al [44] found that herbivore pressure on I. glandulifera in the introduced range increased with age of populations, with the highest levels noted for those 45-65 years old. However, herbivore pressure for the oldest populations (65-85 years) sharply fell to the lowest level, equal to the level noted for native populations.…”
Section: Discussionsupporting
confidence: 90%
“…Gruntman et al [44] showed that the post-introduction herbivore resistance of I. glandulifera rises with time, while its allelopathic effects do not. They further stressed the need for more investigation, citing their earlier finding that the allelopathic ability of the species significantly evolved in the invaded range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, geographic variation in various environmental factors along latitude (north vs. south) seem to be insufficient to explain all observed patterns. Finally, because all of the plants examined in the present study were grown from first‐generation seeds, the influence of maternal effects cannot be completely ruled out (Agrawal et al, ; Gruntman, Segev, Glauser, & Tielbörger, ). Nevertheless, we argue that maternal effects are an unlikely explanation because such effects on plant defence are typically short‐lived, functioning very early in the development of progeny (Agrawal, ; Didiano et al, ; Stanton, ; Turley et al, ), and thus are not expected to persist throughout the course of the about 9‐week common garden experiments conducted in our study.…”
Section: Discussionmentioning
confidence: 99%
“…, Gruntman et al. ), an evolutionary shift in resistance could help alien plants to become invasive when it helps them overcome biotic resistance from newly encountered generalists. In apparent contrast to our finding, another recent meta‐analysis by Felker‐Quinn et al.…”
Section: Discussionmentioning
confidence: 99%